Internal force calculation and supporting parameters sensitivity analysis of side piles in the subway station excavated by Pile-Beam-Arch method. (June 2016) - Liu, Xinrong; Liu, Yongquan; Qu, Wanbo; Tu, Yiliang
Highlights: Deducing the internal force calculation formula for side piles in most adverse state. Designing a test apparatus that can model the actual loading state of side piles. Variation rule of bending moment and displacement to three supporting parameters. Obtaining critical sensitivity values of pile diameter, spacing and buried depth. Comparing the displacement control effect between pile diameter and pile spacing. Abstract: The Pile-Beam-Arch (PBA) excavation method is widely used in subway station construction for it greatly reduces ground settlement caused by excavation. The stress state of side piles is extremely complex in the supporting system of the subway station excavated by PBA method. This paper deduces the internal force calculation formula for side piles under the most unfavorable loading state with the vertical force considered. Testing apparatus which can model the actual loading state of side piles are designed. Single-factor sensitivity analysis is conducted by means of the reduced-scale model test and numerical simulation to study the three supporting parameters (i.e. pile diameter, pile spacing and buried depth). Results indicate that: the additional bending moment induced by the vertical load at the pile top should be considered in internal force calculation of side piles; values from the deduced theoretical calculation formula agree with the test values; horizontal displacement of the pile body reduces significantly and the bending moment increases greatly with the increase of pile diameter or the decrease of pile spacing; the pile bottom basically meets the constraint condition of the fixed end when the buried depth is two times of the excavation depth. Under the test conditions of this paper, critical sensitivity values of three supporting parameters, i.e. pile diameter, pile spacing and buried depth, are respectively 32 mm, 2d (pile diameter) and 2h (excavation depth). It's more economical and effective to adopt the scheme of increasing pile diameter than the scheme of narrowing pile spacing when there's a high requirement for displacement control of side piles.